Cochlear implant failures and reimplantation: A 30‐year analysis and literature review. (21st May 2019) - Lane, Ciaran; Zimmerman, Kim; Agrawal, Sumit; Parnes, Lorne
Abstract : Objectives/Hypothesis: The objectives of the study were to present an institutional experience with device failures and cochlear reimplantation rates over a 30‐year period and to perform a detailed literature review. Study Design: Retrospective institutional experience and literature review. Methods: A review of cochlear implant failures over a period of 30 years, between January 1988 and March 2017, at a single institution was conducted. Cochlear implant failures were calculated based on manufacturer, type of failure, and overall failure rate. Survival analysis was performed using Kaplan‐Meier curves. An electronic search of the PubMed, Web of Science, and EMBASE databases revealed 24 articles on the topic of cochlear device failure. Data on reimplantation and device failure rates were extracted from this literature review and analyzed. Results: A total of 804 cochlear implantations were reviewed from three manufacturers. The institutional reimplantation rate was 2.9% compared to the pooled rate of 6.0% calculated from the literature review. Medical failures accounted for 0.5% of the overall failures, device failures accounted for 1.6%, and inconclusive failures account for 0.7%. Survival analysis revealed a significant difference among manufacturers. An improved device failure rate was noted in the adult population (0.8%) as compared to the pediatric population (2.8%). Conclusions: This 30‐year review represents one of the longest series in the literature examining reimplantation, device failure, and medical failure rates. Cochlear implant survival varied by manufacturer and was significantly better in adult compared to pediatric patients. Level of Evidence: NA Laryngoscope, 130:782–789, 2020